Management of over retention of permanent incisor impacted by compound odontoma: Clinical, radiological, and microscopic evaluation. Issue 2 (August 2018) - Bastos, Valéria de Abreu da Silva; Freitas-Fernandes, Liana Bastos; Soares, Daniela Novaes; Neto, Oswaldo C.; Abrahão, Aline Corrêa; Farinhas, João Alfredo; Fidalgo, Tatiana Kelly da Silva; Primo, Laura Salignac de Souza Guimarães
Abstract: Objective: This case report describes the management of primary tooth over retention and permanent impacted tooth a compound odontoma and the microscopic evaluation. Case report: At 11-years-old, the child was referred for Pediatric Dentistry due to lack of permanent maxillary left central incisor. Radiographic examination revealed over retention of primary maxillary left central incisor associated to a mixed lesion showing tooth-like structures in region of permanent maxillary central left incisor. The primary overretained tooth and the 6 denticles, characterized as compound odontoma, were surgically removed and impacted central incisor was placed in orthodontic traction over a period of 10 months. Odontoma histological characterization was carried out through Hematoxilin and Eosin coloration, polarized light microscopy, and scanning electron microscopy. Small tooth like structures with well defined enamel and dentin could be seen. Conclusion: Orthodontic management was successfully performed for correct alignment of the maxillary left central incisor impacted by compound odontoma reestablishing function, phonation, and esthetic.